Soil Respiration, Microbial Biomass and Ratios (Metabolic Quotient and Mbc/Toc) As Quality Soil Indicators in Burnt and Unburnt Aleppo Pine Forest Soils - Hedo, Javier; Lucas-Borja, Manuel Esteban; Wic, Consuelo; Abellán, Manuela Andrés; Heras, Jorge de Las (Journal of Forests, 2014)
Wildfires affecting forest ecosystems and post-fire silvicultural treatments may cause relevant changes in soil properties. Soil plays an important role in the fertility and stability of the forest ecosystem [1] as it highlights the microorganisms that accomplish reactions to release soil nutrients for vegetation development [2]. Wildfires and post-fire silvicultural treatments may cause relevant changes in forest and soil properties [3, 4]. Fire may alter physical-chemical soil properties (i.e., soil organic matter content and its structure, hydrophobicity, pH and nutrient cycles) [5], microbiological and biochemical soil properties (i.e., microbial biomass, microbial activity, soil enzymes activities) [5]. Long-term studies into soil quality, or which evaluate soil recovery capacity after forest fires or post-fire silvicultural treatments, are scarce. To evaluate soil quality, the use of a general character parameter like soil respiration is commonly used [6, 7]. This study aimed to investigate soil respiration, microbial biomass and ratios (metabolic and MBC / TOC) in burnt and unburnt soils of an Aleppo pine forest ecosystem affected by a wildfire event 17 years ago. It is noteworthy that we define recovery as a scenario which returns to the same activity levels before wildfire perturbation. Our results demonstrated that 17 years after the fire event occurrence, the quality of the burnt soils reached the undisturbed soil levels.